Proteomic analysis of hypoxia‐induced U373MG glioma secretome reveals novel hypoxia‐dependent migration factors. Issue 12 (16th May 2014) - Yoon, Jong Hyuk; Kim, Jaeyoon; Kim, Kyung Lock; Kim, Do‐Hyeon; Jung, Sun‐Ju; Lee, Hyeongjoo; Ghim, Jaewang; Kim, Dayea; Park, Jong Bae; Ryu, Sung Ho; Lee, Taehoon G.
<x xml:space="preserve">Abstract</x> High‐grade gliomas are one of the most common brain tumors and notorious for poor prognosis due to their malignant nature. Gliomas have an extensive area of hypoxia, which is critical for glioma progression by inducing aggressiveness and activating the angiogenesis process in the tumor microenvironment. To resolve the factors responsible for the highly malignant nature of gliomas, we comprehensively profiled the U373MG glioma cell secretome—exosome and soluble fraction under hypoxic and normoxic conditions. A total of 239 proteins were identified from the exosome and soluble fractions. Vascular endothelial growth factor, stanniocalcin 1 (STC1) and stanniocalcin 2, and insulin‐like growth factor binding protein 3 and 6, enriched in the soluble fraction, and lysyl oxidase homolog 2 enriched in the exosomal fraction were identified as upregulated proteins by hypoxia based on a label‐free quantitative analysis. STCs and insulin‐like growth factor binding proteins, which were identified as secretory proteins under hypoxic conditions, were highly correlated with glioma grade in human patients by microarray analysis. An in vitro scratch wound assay revealed that STC1 and 2 have important functions in the induction of cell migration in a hypoxia‐dependent manner, suggesting that they are hypoxia‐dependent migration factors.